Novels as reflections of cultural life in Malaysian society - Nik Affendi, Nik Rafidah; Abd Rahim, Normaliza; Sujud, Arbaie (The International Journal of Learning, 2008)
Novels are considered as social culture documents because they are able to reflect the culture of life of Malaysian society. Generally, culture is a way of life or practical life of a society. The person who appears in the novel is an expression of a human in reality. The actions of a person in a novel are an expression of actions of a human in reality. Thoughts, feelings and actions in a decision made for a specific situation is the actual expression from the reality of a society. As a novel which is a reflection from the world, we can see various culture of life of the Malaysian society from the social, economy and political aspects. Among them, they are very united although they are of various races with different culture of life. These elements of culture enable the three major races in Malaysia, the Malays, Indians and Chinese, to live in peace and harmony.